The selection of IBS precast manufacturing plant in Malaysia using GIS - Azman, Mohamed Nor Azhari; S Ahamad, Mohd Sanusi; Abd Hamid, Zuhairi; Gomez, Christy P; Mohamad Kamar, Kamarul Anuar; Hilmi, Nur Diyana; Mansor, Hezil; Ismail, Zulkefle (Construction Research Institute of Malaysia, 2012)
In Malaysia, the prefabrication technology is known as industrialised building system (IBS) which is defined as a complete process system of construction works where almost all the component structures is manufactured onsite or offsite, and the product is transported to the site and to be installed in the high precision coordinate joint as well as achieve high quality works, and accelerate the time of completion of the projects.The benefits of prefabrication helped the Housing Ministries in various countries to fulfil the high demand for housing especially in the United States, United Kingdom, Australia, Singapore, Hong Kong and Malaysia. Providing affordable homes are becoming a vital issue to meet the increasing demand of IBS components with the policy enforcement in ensuring the continuous demand. The most popular IBS component used in Malaysia is precast components. Over the years, the total number of IBS precast manufacturers has increased from15 in 2009 to 36 factories in 2011. Geographical Information System (GIS) can be seen as an important tool in finding new locations for IBS precast manufacturing. This paper introduced a conceptual GIS suitability model by applying six criterion factors i.e. road characteristic, proximity from the new potential development area, population census, proximity from the existing infrastructure, topography and land-use suitability. Results shows that 16 out of 25 IBS precast manufacturers with ongoing production are located in Selangor, Johor and Negeri Sembilan. However, there are still good opportunities in expanding IBS businesses in other states where the number of IBS precast manufacturers are still low.